Theoretical study of copper corrosion prevention by terpenoid green inhibitors of thymol, carvacrol, and thymohydroquinone - Hadisaputra Saprizal; Abhi Purwoko Agus; Hakim Aliefman; Hamdiani Saprini (E3S Web of Conferences, 2024)
Electronic parameters have been used to predict the corrosion inhibition performance of the green inhibitors of thymol, carvacrol, and thymohydroquinone against copper. Molecular modeling was carried out at the density functional and ab initio levels and Monte Carlo molecular dynamics. Tymohydroquinone can prevent copper corrosion better than the other two monoterpenoids. Molecular dynamics studies show that corrosion inhibitors are adsorbed on the metal surface, thereby inhibiting corrosion from occurring on the metal surface.